Efficacy Of Articaine And Lidocaine For Local Anesthesia In Tooth Extraction: A Systematic Review - Asmara’Nda Dara Puspita; Dendy Murdiyanto (International Journal of Health Engineering and Technology, 2026)
Pain is one of the main obstacles in tooth extraction procedures; therefore, effective local anesthesia is required to improve patient comfort during the procedure. Lidocaine is the most commonly used local anesthetic in dentistry, while articaine has increasingly been used because it is claimed to have better tissue diffusion ability and a longer duration of action. This systematic review aimed to determine the effectiveness of articaine compared with lidocaine as a local anesthetic in tooth extraction procedures. The method used was the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) with article searches conducted through the ScienceDirect, PubMed, and Scopus databases using the keywords “Lidocaine AND Articaine AND Tooth Extraction.” The inclusion criteria included randomized controlled trial (RCT) articles, articles published in English between 2015 and 2025, and studies discussing the use of lidocaine and articaine in tooth extraction procedures. From the search results, 797 articles were identified, and after the selection process, 6 articles met the inclusion criteria. The review results showed that articaine has several advantages over lidocaine, including no need for additional injection volume, faster onset of action, longer anesthetic duration, and lower intraoperative and postoperative pain complaints. Based on these findings, it can be concluded that articaine is a more effective local anesthetic than lidocaine for tooth extraction procedures.